2018
DOI: 10.1159/000493895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hawthorn Leaf Flavonoids in Dehydroepiandrosterone-Induced Polycystic Ovary Syndrome in Rats

Abstract: Objective: To evaluate the potential beneficial effects of hawthorn leaf flavonoids (HLF) against polycystic ovary syndrome (PCOS) in a rat model of disease and elucidate the underlying molecular mechanism. Methods: The PCOS model was established by subcutaneous injection of dehydroepiandrosterone (DHEA, 60 mg/kg/day) for 21 consecutive days. HLF (200 mg/kg/day) were orally administered simultaneously or after the injection. The body weight was regularly monitored and recorded. The ovaries were weighed and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Hawthorn leaf flavonoids are the extract of the hawthorn dry leaves of Rosaceae . It possesses antioxidant, anti-inflammatory, and hypolipidemic activities [ 65 ]. Hawthorn leaf flavonoids were found to enhance the activity of antioxidant enzymes and inhibit the oxidative modification of LDL-C, while also improving oxidative stress-induced damage to the rat myocardium through the PKC-alpha signaling pathway.…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…Hawthorn leaf flavonoids are the extract of the hawthorn dry leaves of Rosaceae . It possesses antioxidant, anti-inflammatory, and hypolipidemic activities [ 65 ]. Hawthorn leaf flavonoids were found to enhance the activity of antioxidant enzymes and inhibit the oxidative modification of LDL-C, while also improving oxidative stress-induced damage to the rat myocardium through the PKC-alpha signaling pathway.…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…Hawthorn leaves have been used to treat cardiovascular and fatty liver diseases ( Yin et al, 2014 ). Hawthorn leaves flavonoids ( HF ), extracted from hawthorn leaves, have been proved to exert antihypertensive action, anti-inflammatory, free radical scavenging, and antimicrobial activities ( Fu et al, 2013 ; Shi et al, 2019 ). A previous study has suggested that HF can alleviate nonalcoholic fatty liver disease by enhancing the adiponectin/AMPK pathway in NAFLD rats ( Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nonalcoholic steatohepatitis ( NASH ) rats are intragastrically administered hawthorn leaves flavonoids improves lipid metabolism and antioxidant capacity by regulating the Nrf2/HO-1 signaling pathway ( Wang et al, 2018a ). The antioxidant and anti-inflammatory effects of HF have also been shown to treat cataracts and polycystic ovaries in rats ( Wang et al, 2011b ; Shi, Kong, Yin, Zhang and Wang, 2019 ). However, the effect of HF on the reproduction performance and lipid metabolism of aged breeder hens remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, mice experienced the promotion of hair growth by taking C. pinnatifida extract through the induction of anagen phase, by mediating cellular signaling activation resulting in high proliferation and survival rate of human dermal papilla cells, as well as by increasing the Bcl-2/Bax ratio, resulting in protection from cell death [146]. Rats with dehydroepiandrosterone-induced polycystic ovary syndrome experienced protective effects due to the consumption of hawthorn leaf flavonoids [147].…”
Section: Anticataract Potentialmentioning
confidence: 99%